KONSEP KELUARGA SAKINAH PASANGAN TIDAK MEMILIKI KETURUNAN DI KOTA LANGSA ACEH - Rasyidin; lestari, Putri Indah (Program Studi Hukum Keluarga Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
This paper focuses on the concept of the sakinah family of couples who do not have children. Domestic life is not from conflicts that arise to differences of opinion between husband and wife, but the most important thing is how to keep the family intact. The different problems that occur are also different ways to solve them, some end in divorce, some lead to harmony. A marriage that is not blessed with offspring does not mean unhappy they are also happy in their own way. As for the formulation of the problem that the author sets, how is the concept of a family without children in building a family, and what are the challenges for couples who do not have children in building a sakinah family? The author uses the type of field research ( field research). The descriptive approach to empirical analysis. The result of this paper is that in building a sakinah family, couples who do not have children have a variety of ways to do it but still have one goal, namely to build a sakinah family. According to them, the concept of a sakinah family is a family based on religion, loving each other, loving each other, trusting each, consulting each if there are problems, and solving them as well as possible so that marriage remains intact. In dealing with problems, there are various ways of solving them but still ending with happiness, because many are not happy because of problems in the household.